Prosthodontic rehabilitation of a patient with missing teeth and loss of vertical dimension using telescopic overdentures - Daniel Arunraj; Padmashini Gnanam; Gopi N Chander (Wolters Kluwer Medknow Publications, 2021)
Overdentures are one of the most sought-after treatment options for patients with few remaining natural teeth. They are desired as they tend to preserve the natural teeth and its intact periodontium. This helps in reducing the residual ridge resorption and preserve proprioception. These characteristics offer better masticatory ability in patients rehabilitated with overdentures when compared to conventional complete dentures. Enhancements such as telescopic denture for better retention prove to be efficient clinically. Telescopic dentures enable frictional type of retention. This is a case report of a partially edentulous patient with decreased vertical dimension, successfully rehabilitated with telescopic denture in relation to the maxilla and fixed partial prosthesis in the mandibular region.